Economic Development and Its Effect on Income Distribution: Evidence from Australia - Haque, Mohammed (2009)
This study involved investigating the progress of economic development and its effects on income distribution in Australia between 1970 and 2000. Results indicate that Australia exhibited good economic development with increased income inequality. The basis of the estimation of the rate of change and elasticity of income inequality was a new functional form (the double semi-log), using Household Expenditure Survey data. Results illustrate that during high economic growth, income inequality increases. Thus, economic development has a significant positive effect on income distribution even in a developed country such as Australia. This research revisits Kuznets’ hypothesis and shows that the inequality of income can increase at any stage of development, not only in the early stages, which Kuznets originally observed.